1997
DOI: 10.1128/aac.41.10.2292
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of cefodizime and ceftriaxone in sera and bones of patients undergoing hip arthroplasty

Abstract: The study was carried out to determine the concentrations of cefodizime (single 2-g intravenous [i.v.] dose) and ceftriaxone (single 2-g i.v. dose) in the sera and bones of 42 patients (18 women and 24 men) undergoing hip arthroplasty. The concentrations of cefodizime and ceftriaxone in cancellous and cortical bone appear to be related to the free levels in serum but not to the total levels in serum, so the concentrations of cephalosporins in bone must be compared with the free concentrations in serum. Both dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Scaglione et al . also observed higher levels of ceftriaxone in cancellous than in cortical bone and explained this by the differences in blood flow [27]. This may also explain the higher uptake rate into cortical bone observed in our study.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Scaglione et al . also observed higher levels of ceftriaxone in cancellous than in cortical bone and explained this by the differences in blood flow [27]. This may also explain the higher uptake rate into cortical bone observed in our study.…”
Section: Discussionsupporting
confidence: 71%
“…This may also explain the higher uptake rate into cortical bone observed in our study. Interestingly, the free levels of ceftriaxone in serum were comparable with the concentrations in bone [27]. The role of the free concentration of ceftriaxone for its concentration in bone was subsequently challenged by others [28].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unlike glycopeptides, streptogramins and linezolid, many later-generation cephalosporins possess good activity against Gram-positive and Gram-negative organisms from all clinical sources [13]. Recent studies have demonstrated that compounds, such as ceftriaxone diffuse well into bone (15-20% of systemic blood concentration), with concentrations exceeding the MIC for methicillin-susceptible staphylococci and the vast majority of other major pathogenic infecting organisms [14,15]. In addition, ceftriaxone due to its favourable pharmacokinetics that allow once-daily dosing, have been recommended for the outpatient treatment of bone infections, in order to reduce the cost of prolonged hospital stays [16].…”
Section: Discussionmentioning
confidence: 99%
“…Scaglione et al measured CFX concentrations in uninfected bone of patients undergoing hip arthroplasty: CFX concentrations in cancellous and cortical bone were dramatically lower than total serum levels, but comparable to serum free levels; maximum observed CFX concentrations were 10.7 and 19.4 mg/kg of body weight in cortical and cancellous bone, respectively, 2.5 h after antibiotic administration. 14 Lovering et al measured bone concentrations of CFX and cefamandole administered simultaneously before total hip replacement: CFX and cefamandole mean bone penetration appeared similar (15.6% vs. 18.4%), providing no evidence that cephalosporins with lower serum protein binding penetrate bone better than ones with higher protein binding. 15 Finally, Soudry et al reported CFX penetration rates varying between 5% and 8% in cortical bone and between 14% and 21% in cancellous bone.…”
Section: Discussionmentioning
confidence: 99%